Implementasi Nilai-nilai Pendidikan Agama Islam dalam Pembentukan Sikap Peduli Lingkungan Siswa MIN 2 Probolinggo - Mery, Unawekla; Abd. Aziz; Muhammad Hifdil Islam (An Naba, 2023)
The purpose of the study is to see how teachers instill the values of Islamic Religious Education and its implementation of students into shaping the nation’s environment of Madrasah Ibtidaiyah (MIN) 2 Probolinggo. In research this approach is done with qualitative methods. Research shows that the implanting of religious values not only takes place when the learning process is under way, but it also does not remove from the shared breeding of religious values for both students and teachers. Like prayer dhuha, tahfidzul qur’an, talent and interest development, the planting of a tree together, natural-based learning, and other programs. Not only students, teachers are required to provide a good example to support the growing of environmental concern in students through religious values. As a paragon in school, teachers should give example of behaviors that reflect religious attitudes, such as greeting in meeting with students or other teachers so that the institution can be see and exemplified by students. Similarly, madrasah’a vision and mission contribute to a crucial point PERMATA LIMA, DISISI BERLIAN (faithful and faithful learners in Allah, bearing faith, gentle, disciplined, caring and culturally).